2010
DOI: 10.1055/s-0029-1243936
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of lymphoid hyperplasia of the lower gastrointestinal tract

Abstract: Lymphoid hyperplasia of the intestine has been associated with multiple diseases and symptoms. This study was undertaken to analyze the number and topographical distribution of the lymphoid follicles. A total of 302 adult consecutive patients were enrolled when they underwent elective colonoscopy. Standardized pictures from terminal ileum and colon were taken using video colonoscopes. In each picture, the number, size, and mucosal elevation of lymphoid follicles were analyzed in relation to histological and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…The term "lymphoid hyperplasia" was first introduced in 1970 by Capitanio & Lirkpatrick to describe numerous lymphoid follicles with an average diameter of 2 mm (9,11,12). Typical endoscopic findings of lymphoid hyperplasia include multiple nodular, closely spaced, yellowish-white polyps measuring 1-2 mm in diameter (9).…”
Section: Hematoxylin and Eosin Staining (A) And Immunostainings (B-e)mentioning
confidence: 99%
See 1 more Smart Citation
“…The term "lymphoid hyperplasia" was first introduced in 1970 by Capitanio & Lirkpatrick to describe numerous lymphoid follicles with an average diameter of 2 mm (9,11,12). Typical endoscopic findings of lymphoid hyperplasia include multiple nodular, closely spaced, yellowish-white polyps measuring 1-2 mm in diameter (9).…”
Section: Hematoxylin and Eosin Staining (A) And Immunostainings (B-e)mentioning
confidence: 99%
“…The term "lymphoid hyperplasia" was first introduced in 1970 by Capitanio & Lirkpatrick to describe numerous lymphoid follicles with an average diameter of 2 mm (9,11,12). Typical endoscopic findings of lymphoid hyperplasia include multiple nodular, closely spaced, yellowish-white polyps measuring 1-2 mm in diameter (9). On the other hand, tumorous lesions of various sizes can occur following the development of lymphoid hyperplasia, as a sequel to marked proliferation of inflammatory cells, although this is a rare pathologic condition, especially in the proximal colon (13,14).…”
Section: Hematoxylin and Eosin Staining (A) And Immunostainings (B-e)mentioning
confidence: 99%
“…When biopsied, these areas always corresponded to clusters of ≤ 10 lymphoid nodules, composed of hyperplastic benign lymphoid tissue, named “nodular lymphoid hyperplasia” (NLH)[5-9]. Sometimes NLH had a reddish outline, the so-called “red ring sign” (RRS), due to hypervascularization at the base of the follicles, associated with granulocyte infiltrate[6]. …”
Section: Introductionmentioning
confidence: 99%
“…Kagueyama et al[31], demonstrated that 39% of adult patients with chronic diarrhoea and a normal colonoscopy had NLH at histological examination of serial biopsies taken from the terminal ileum, ascending colon and rectum. In 2010, Krauss et al[6] evaluated the significance of lymphoid hyperplasia in the lower gastrointestinal tract in a cohort of consecutive adult patients and concluded that the presence of colonic NLH is not rare and it may represent a mucosal response to antigenic stimulation, like allergens or pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Marked areas of right-sided colonic erythema and pronounced hyperplasia of lymphoid follicles were detected along the lower gastrointestinal tract. Increased numbers of lymphoid follicles were detected (≥10 -15/high-powered field [HPF]; normal ≤ 8) [1] using the high-resolution CCD (charge-coupled device) chip and FICE (Fuji intelligent color enhancement) (• " Fig. 2 a, b), and were clearly shown by chromoendoscopy with methylene blue (• " Fig.…”
mentioning
confidence: 99%